Between Ibn Khaldun and Ibn Tamiyya: Islamic Socio-Political Ideal and Dynastic Autocracy (Reflections on the Tide of “Arab Spring”) - Alexeev, Igor (İbn Haldun Çalışmaları Dergisi, 2017)
Comparing Ibn Khaldun’s theory with extensive material accumulated by historians and anthropologists who studied the phenomenon of symbiosis between nomadic and sedentary societies of the Middle East, North Africa and Central Eurasia, one may argue that in fact, Ibn Khaldun has created a generalized theoretical model of the particular society in which he lived and which he knew very well. Fortunately, Islamic culture provides us an example of authentic social theory of traditional Muslim society, developed on the base of classical Muslim historiography, i.e. the theory of ‘Abd al-Rahman Ibn Khaldun (1332 – 1406).